Determination of morin in maclura cochinchinensis heartwood by HPLC - Kongkiatpaiboon S. (2017)
© The Author 2016. Published by Oxford University Press. All rights reserved. The HPLC-DAD method was developed to determine morin content in Maclura cochinchinensis Corner heartwood extract. The chromatographic separation was performed using a Hypersil BDS C18 column, isocratic solvent system of 0.5% acetic acid in water:acetonitrile (80:20) with 1.0mL/min flow rate and detected at 355 nm. The standard curve of morin was linear in the range of 7-905 μg/mL. The method was precise with intra-day relative standard deviation (RSD) of lower than 1% and 2.06% for inter-day RSD. The method accuracy represented by percent recover was 99.58%. The highly efficient HPLC system developed from this study could detect morin contents in M. cochinchinensis heartwood samples collected from various locations in Thailand in the range of 0.74-1.57% w/w. This developed method provided a useful standardization procedure of M. cochincihinesis materials for further application in pharmacy and other commercial developments.